Humidity sensor using surface adsorbed channel modulated Graphene nanoribbon: NEGF approach - Shakil, Shifur Rahman; Zohra, Fatema Tuz; Pramanik, Parna; Tushar, Raihanul Islam (© 2014 Institute of Electrical and Electronics Engineers Inc., 2017)
This conference paper was presented in theInternational Conference on Electrical and Computer Engineering, ICECE 2014; Pan Pacific Sonargaon DhakaDhaka; Bangladesh; 20 December 2014 through 22 December 2014 [© 2014 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICECE.2014.7026951